Intersectionality as embodiment - Sune Qvotrup Jensen (The Royal Danish Library, 2010)
Intersectionality as embodiment. This article explores intersectionality as embodiment, arguing that by taking embodiment into account broader possibilities of intersectional analysis can be unfolded. Inspired by phenomenological theories of embodied experience and the mimetic faculty, the article suggests that intersectionality can be understood as embodied experience. Following this thinking embodiment is radically conditioned as well as a site of agency. This has implications for the understanding of structures, agency as well as their interrelation.